PENGARUH MEDIA FOTOGRAFI PADA PEMBELAJARAN IPA TERHADAP HASIL BELAJAR SISWA KELAS V SDN KOTA BENGKULU - Achmad Dzaky; Feri Noperman; Victoria Karjiyati (JURIDIKDAS, 2022)
This study aimed to find out the effect of photography media for Natural Science lesson on the 5th grade elementary students' learning outcomes in Bengkulu City. This study was a quantitative study. The research method applied was a quasy experiment with the matching only pretest-posttest control group design. The population for this research was all elementary schools in Bengkulu City with B accreditation and it was obtained that SDN 77 Bengkulu City and SDN 50 Bengkulu City were selected as the samples. The sampling technique was cluster random sampling. The samples for this study were Class VB of SDN 77 Bengkulu City as the experimental class, and Class VB of SDN 50 Bengkulu City as the control class. The instrument used in this study was a test sheet in the multiple choice form. The test was conducted two times which were before and after the learning process in both of the experimental and control class. The data analysis technique implemented were descriptive statistical analysis and inferential analysis which was t-test. The result data processed by t-test showed the value of tcalculation (4.93) and the value of ttable (1.67) on the 5% significance level, statistically it was seen that tcalculation (4.93) > ttable (1.67). Thus, it may be concluded that there is some effect of photography media for Natural Science lesson on the 5th grade elementary students' learning outcomes in Bengkulu City.